THE ROLE OF SEMANTICS IN LANGUAGE UNDERSTANDING: A CASE STUDY OF SERANG JAVANESE IN CIRUAS DISTRICT, SERANG REGENCY - Haidar Alfaqih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study will discuss the role of semantics in language comprehension with the object of study being Serang Javanese. In this study, the researcher used a qualitative research method, with the type of field research. And the source of information in this study was obtained by the researcher through observation and interviews as primary data sources. In this study, the researcher used an ethnographic approach which is indeed appropriate for what the researcher did. In this study, the Serang Javanese language (BJS), which is a local language whose speakers are spread across areas such as Cilegon, Serang Regency, and Serang City, has several unique features and deep meanings. The role of semantics and pragmatics can support the understanding of researchers and readers how phrases (BJS) have deep meanings and are not limited to phrases that have literal meanings alone, but must see the contexts in which they occur.